Nickel-Responsive Induction of Urease Expression in Helicobacter pylori Is Mediated at the Transcriptional Level - van Vliet, Arnoud H. M. (American Society for Microbiology, 2001)
The nickel-containing enzyme urease is an essential colonization factor of the gastric pathogen Helicobacter pylori, as it allows the bacterium to survive the acidic conditions in the gastric mucosa. Although urease can represents up to 10% of the total protein content of H. pylori, expression of urease genes is thought to be constitutive. Here it is demonstrated that H. pylori regulates the expression and activity of its urease enzyme as a function of the availability of the cofactor nickel. Supplementation of brucella growth medium with 1 or 100 μM NiCl(2) resulted in up to 3.5-fold-increased expression of the urease subunit proteins UreA and UreB and up to 12-fold-increased urease enzyme activity. The induction was specific for nickel, since the addition of cadmium, cobalt, copper, iron, manganese, or zinc did not affect the expression of urease. Both Northern hybridization studies and a transcriptional ureA::lacZ fusion demonstrated that the observed nickel-responsive regulation of urease is mediated at the transcriptional level. Mutation of the HP1027 gene, encoding the ferric uptake regulator (Fur), did not affect the expression of urease in unsupplemented medium but reduced the nickel induction of urease expression to only twofold. This indicates that Fur is involved in the modulation of urease expression in response to nickel. These data demonstrate nickel-responsive regulation of H. pylori urease, a phenomenon likely to be of importance during the colonization and persistence of H. pylori in the gastric mucosa.